Vitamin D Receptor Gene Polymorphisms in Rheumatoid Arthritis - Ömer ATEŞ,; Bilgen DÖLEK,; Levent DALYAN,; Ayşegül Topal-SARIKAYA, (Archives of Rheumatology, 2011)
Objectives: In this study, we investigated the association of BsmI, TaqI, and FokI polymorphisms in the vitamin D receptor gene in rheumatoid arthritis patients with rheumatoid factor positivity and erosive disease of rheumatoid arthritis. Patients and methods: In this study we analyzed BsmI, TaqI and FokI polymorphisms in the vitamin D receptor gene in 98 patients with RA (78 females, 20 males; mean age 50.8±12.3 years; range 38 to 63 years) and 122 healthy subjects (96 females, 26 males; mean age 57.1±6.1 years; range 51 to 63 years) by a polymerase chain reaction followed by enzymatic digestion between May 2006 and April 2008. Results: The distributions of BsmI, TaqI and FokI, alleles/genotypes frequencies were similar in patients and controls. There were no significant differences between the vitamin D receptor genotypes/alleles and the presence or absence of erosions and rheumatoid factor. Conclusion: Our findings suggest that vitamin D receptor polymorphisms do not play a role in either rheumatoid arthritis susceptibility or in rheumatoid factor positivity and erosive disease of rheumatoid arthritis in the Turkish population.